High availability MySQL cookbook : over 50 simple but incredibly effective recipes focusing on different methods of achieving high availability for MySQL databases /: over 50 simple but incredibly effective recipes focusing on different methods of achieving high availability for MySQL databases. (2010) - Unknown
No abstract available